Ideas in Time The longue durée in Intellectual History - Potts, John (Sociétés contemporaines, 2019)
Ideas In Time deals extensively with the history of ideas. The aims of the book are: to provide a coherent theoretical account of the ill-defined field known as 'the history of ideas'; to emphasise the longue durée or long view in intellectual and cultural history; to develop a reconfigured history of ideas, attentive both to the endurance of certain ideas and beliefs, and to breaks and shifts in meaning over time; and to support this general ambition with studies of specific ideas over long durations, namely: the ideas of progress, democracy, zero, charisma, the Olympic games, and the idea of the West. Ideas in Time emphasises both historical continuity and discontinuity, drawing on both perspectives in its reconstruction of the history of ideas. This theoretical model entails the possibility of tracing the history of certain ideas from their ancient origins to their present expression, while acknowledging alterations in meaning determined by changing social and cultural contexts.